2012
DOI: 10.1021/jm300385f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Study of 2-(Pyrrolesulfonylmethyl)-N-arylimines: A New Class of Inhibitors for Human Glutathione Transferase A1-1

Abstract: Overexpression of human GSTA1-1 in tumor cells is part of MDR mechanisms. We report on the synthesis of 11 pyrrole derivatives as hGSTA1-1 inhibitors starting from 1-methyl-2-[(2-nitrobenzylsulfanyl]-1H-pyrrole. Molecular modeling revealed two locations in the enzyme H binding site: the catalytic primary one accommodating shorter and longer derivatives and the secondary one, where shorter derivatives can occupy. Derivative 9, displaying the highest inhibition and bearing a p-nitroarylimino moiety, and derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 56 publications
3
15
0
Order By: Relevance
“…This is in agreement with earlier observations 34 and has been confirmed by kinetic studies with our enzyme preparation, using BSP as an inhibitor and CDNB as a variable substrate, demonstrating a non-competitive modality of inhibition. 13,19 In designing the enzyme assay protocol for screening the compounds as potential hGSTA1-1 inhibitors, the concentration of 25 lM, falling within the 1-30 lM range, suggested in bibliography as an appropriate one for inhibitor screening, 35 has been chosen. A more crucial factor to be decided has been the substrate concentration, [ 35 In contrast, if we were to run the enzyme assays at relatively high substrate concentrations (i.e., high [CDNB]/K m values), we would bias the screening assay against competitive inhibitors, in favour of uncompetitive ones, whereas the inhibition potency of noncompetitive inhibitors would not be affected by the ratio outcome.…”
Section: Screening Of the Compounds And Selection Of 'Lead Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with earlier observations 34 and has been confirmed by kinetic studies with our enzyme preparation, using BSP as an inhibitor and CDNB as a variable substrate, demonstrating a non-competitive modality of inhibition. 13,19 In designing the enzyme assay protocol for screening the compounds as potential hGSTA1-1 inhibitors, the concentration of 25 lM, falling within the 1-30 lM range, suggested in bibliography as an appropriate one for inhibitor screening, 35 has been chosen. A more crucial factor to be decided has been the substrate concentration, [ 35 In contrast, if we were to run the enzyme assays at relatively high substrate concentrations (i.e., high [CDNB]/K m values), we would bias the screening assay against competitive inhibitors, in favour of uncompetitive ones, whereas the inhibition potency of noncompetitive inhibitors would not be affected by the ratio outcome.…”
Section: Screening Of the Compounds And Selection Of 'Lead Structuresmentioning
confidence: 99%
“…Therefore, several drugs and prodrugs, acting as inhibitors against GSTs, have been proposed to overcome MDR attributed to GST overexpression. 17 GST-inhibiting strategies, focusing on ethacrynic acid analogues, 18 individual compounds 17,19 and prodrug molecules 20,21 have been employed. Several GSH analogues have also been proposed as more specific GST inhibitors, 22 exploiting the high affinity of GSTs for the tripeptide substrate GSH.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, several synthetic drugs and prodrugs with inhibition potency against GSTs have been developed for tackling GST‐attributed multiple drug resistance . Ethacrynic acid and its analogues, individual compounds, and prodrugs have been examined as GST inhibitors. Furthermore, various GSH analogues have been considered as reversible and irreversible inhibitors against GSTs, exploiting the high affinity of the physiological tripeptide substrate GSH for GSTs.…”
Section: Introductionmentioning
confidence: 99%
“…Human cytosolic GSTs, on the basis of their amino acid sequence, can be divided into the following eight classes: alpha , mu , pi , sigma , theta , zeta , kappa and omega [1][5]. Structural studies have shown that GSTs are dimeric enzymes with each subunit containing a GSH-binding site (G-site) and a second adjacent hydrophobic binding site for the electrophilic substrate (H-site) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Various electrophilic xenobiotics are used as substrates by GSTs. Electrophilic centres for GSH conjugation are found in areneoxides, aliphatic and arylic halides, in carbonyls, organonitro-esters, organic thiocyanates, including certain chemotherapeutic drugs [3], [5], [6]. Identification of the GST-mediated pathway for drug cleavage has been useful for elucidating the mechanism of metabolic biotransformation of compounds that have been brought forward for clinical studies and, furthermore, enables the design of new molecules that exhibit improved efficacy and pharmacokinetic characteristics [11], [12].…”
Section: Introductionmentioning
confidence: 99%